APPLICATION OF 3D MODELING IN HUMAN ACTIVITY (Modern information system and technologies, 2018)
The article is devoted to the review of methods and methods of using computer 3D modeling in various spheres of human life. The evolution of computer technology leads to the emergence of new opportunities. 3D models are used in contemporary cinematography, architecture, advertising, computer games, medicine, and more. In the article we will discuss the peculiarities of the creation of special effects, the technical complexity of the modeling process of 3D objects. Keywords: 3D, model, visualization, polygons, graphics, texture.